The effects of increase and variations in time presentations for second language vocabulary learning - Radina, Mohamad Deli; Zainab, Ghareeb-Ali; Shorouk, Al-Houti (Issues in Language Studies, 2013)
Barcroft (2007) found opportunities for word retrieval to be advantageous during second language vocabulary learning. This study extended such a finding and investigated the effect of increased time in target-word retrieval for learning new vocabulary in the L2, as well as the effect of presentation orders of different time conditions on word retrieval. The data were obtained from 17 native Arab speakers who attempted to learn 24 new English words by viewing 24 word-picture pairs. Each picture and its corresponding word were viewed with different time lags of 0, 6 and 12 seconds between them in different presentation orders. The results showed that, although the increased time does not positively affect word retrieval, the overall findings correspond to Barcroft’s (2007) view, at least in the case of 6 seconds lag. The results also showed that the production of target words in both the control and retrieval-oriented conditions depend on and vary according to the order of presentation, particularly in the case of 6 seconds lag in which word gain is found to be highest when the lag is presented first and second.